Contrastive Causative Construction in Japanese and Indonesian: X-Bar Theory - Arfianty, Rani (International Journal Linguistics of Sumatra and Malay, 2024)
This study aims to describe causative contractions in Japanese and Indonesian; how causative sentence structures in the form of diagrams through X-Bar theory, their meanings in Japanese and Indonesian, as well as their similarities and differences in both languages. The study used contrastive analysis to compare the causal sentence contraction of both languages. Research results show that the causal sentence construction of both languages is derived from non-causative sentences by converting predicates into causative verbs. However, there are several verbs in both Indonesian and Japanese, which already have a causative meaning, such as korosu (killing), akeru (opening), mawasu (spinning), and others. The causative construction of the Indonesian language is composed of three types: lexical causative, morphological causative, and paraphrastically causative. Japanese causative construction is only in lexical causative, and paraphrastically causative. The causative Japanese sentences are marked by the pronunciation of o-saseru and ni-saseru in intransitive verbs and transitive verbs at the end of the sentence. Also, ni and o-saseru appear in the same sentence as transitive verbs. Causative sentences of Indonesian can be formed by affixing ikan, -i, per-. The basic structure of Indonesian causative sentences is formed from inflections, spacer and verb phrases. The initial structure, predominantly FI over FV then, moved to the [Ses FP] position in its derivative structure.